World Bank Research Digest, Vol. 5(1) - World Bank (Washington, DC, 2014)
In this issue: charting new directions in development economics; focus: agriculture for development, revisited; too big to fail or too big to save? Bank runs in emerging economies; closer scrutiny of mashup indices; ethnic discrimination and political competition in Sri Lanka; and interactions between formal and informal institutions.